Albatross/FBF1 contributes to both centriole duplication and centrosome separation. (13th November 2018) - Inoko, Akihito; Yano, Tomoki; Miyamoto, Tatsuo; Matsuura, Shinya; Kiyono, Tohru; Goshima, Naoki; Inagaki, Masaki; Hayashi, Yuko
Abstract: The centrosome is a small but important organelle that participates in centriole duplication, spindle formation, and ciliogenesis. Each event is regulated by key enzymatic reactions, but how these processes are integrated remains unknown. Recent studies have reported that ciliogenesis is controlled by distal appendage proteins such as FBF1, also known as Albatross. However, the precise role of Albatross in the centrosome cycle, including centriole duplication and centrosome separation, remains to be determined. Here, we report a novel function for Albatross at the proximal ends of centrioles. Using Albatross monospecific antibodies, full‐length constructs, and siRNAs for rescue experiments, we found that Albatross mediates centriole duplication by recruiting HsSAS‐6, a cartwheel protein of centrioles. Moreover, Albatross participates in centrosome separation during mitosis by recruiting Plk1 to residue S348 of Albatross after its phosphorylation. Taken together, our results show that Albatross is a novel protein that spatiotemporally integrates different aspects of centrosome function, namely ciliogenesis, centriole duplication, and centrosome separation. Abstract : Protein–protein interactions involved in the centrosome cycle (Adapted from "Regulating the transition from centriole to basal body", The Journal of Cell Biology, Vol. 193, No. 3, p436). Full‐length Albatross was confirmed to contribute to ciliation (1), and the C‐terminus and the N‐terminus of Albatross were found to interact with the Plk4‐STIL‐HsSAS‐6 complex and Plk1 for centriole duplication (2) and centrosome separation (3), respectively.